A numerical approach to investigating the mechanisms behind tonotopy in the bush-cricket inner-ear - Celiker, Emine; Woodrow, Charlie; Mhatre, Natasha; Montealegre-Z, Fernando (Frontiers in Insect Science, 2022)
Bush-crickets (or katydids) have sophisticated and ultrasonic ears located in the tibia of their forelegs, with a working mechanism analogous to the mammalian auditory system. Their inner-ears are endowed with an easily accessible hearing organ, the crista acustica (CA), possessing a spatial organisation that allows for different frequencies to be processed at specific graded locations within the structure. Similar to the basilar membrane in the mammalian ear, the CA contains mechanosensory receptors which are activated through the frequency dependent displacement of the CA. While this tonotopical arrangement is generally attributed to the gradual stiffness and mass changes along the hearing organ, the mechanisms behind it have not been analysed in detail. In this study, we take a numerical approach to investigate this mechanism in the Copiphora gorgonensis ear. In addition, we propose and test the effect of the different vibration transmission mechanisms on the displacement of the CA. The investigation was carried out by conducting finite-element analysis on a three-dimensional, idealised geometry of the C. gorgonensis inner-ear, which was based on precise measurements. The numerical results suggested that (i) even the mildest assumptions about stiffness and mass gradients allow for tonotopy to emerge, and (ii) the loading area and location for the transmission of the acoustic vibrations play a major role in the formation of tonotopy.